2011
DOI: 10.1002/ange.201101378
|View full text |Cite
|
Sign up to set email alerts
|

Die CO‐Oxidation als Modellreaktion für heterogene Prozesse

Abstract: Die CO‐Oxidation, obwohl eine scheinbar einfache chemische Reaktion, dient als ein Modell, welches die Vielfalt und Attraktivität der heterogenen Katalyse offenbart. Das Fritz‐Haber‐Institut ist ein Ort, an dem ein multidisziplinärer Forschungsansatz zum Studium einer solchen heterogenen Reaktion innerhalb eines Instituts entwickelt und umgesetzt werden kann. Dabei ist die Forschung am Institut primär durch Neugier getrieben, was sich auch in den fünf Abschnitten dieses Aufsatzes widerspiegelt. Wir nutzen dabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(17 citation statements)
references
References 202 publications
(223 reference statements)
0
17
0
Order By: Relevance
“…Arguably,t he metal-mediated CO!CO 2 conversion is one of the most often studied systems,both at surfaces [39] and in the gas phase. [40] In recent years,the focus of interest shifted from the investigation of homonuclear to "doped" clusters,as it turned out that even seemingly simple phenomena, such as adsorption energies,d issociative versus physical adsorption, and cluster reorganization or cluster fragmentation upon landing of CO,c rucially depend on the composition of the heteronuclear clusters.…”
Section: Oxidation Of Co Under Ambient Conditionsmentioning
confidence: 99%
“…Arguably,t he metal-mediated CO!CO 2 conversion is one of the most often studied systems,both at surfaces [39] and in the gas phase. [40] In recent years,the focus of interest shifted from the investigation of homonuclear to "doped" clusters,as it turned out that even seemingly simple phenomena, such as adsorption energies,d issociative versus physical adsorption, and cluster reorganization or cluster fragmentation upon landing of CO,c rucially depend on the composition of the heteronuclear clusters.…”
Section: Oxidation Of Co Under Ambient Conditionsmentioning
confidence: 99%
“…These UHV-studies have been recently complemented by investigations in our group on more realistic catalysts [10,11]. Post-synthesis treatment of co-precipitated Pd/iron oxide catalysts was found to be crucial for the induction of phase-transition in the supporting iron oxide (from Fe 2 O 3 to Fe 3 O 4 polymorph).…”
Section: Introductionmentioning
confidence: 95%
“…The same observations were made by Johnson et al [28] who investigated CO-oxidation and CO-adsorption on ␣-and ␤-PdZn and observed 5-10 times higher initial rates for the reaction, compared to pure Pd, however observing also deactivation upon time by zinc oxidation. CO-oxidation in general was intensively studied and discussed as a suitable model reaction for various heterogeneous, catalytic processes [29]. In the present work we study the role of SMSI in the Pd/ZnO system, by applying a similar, methodological approach, recently applied on the Pd/Fe 2 O 3 system [30]: the change of activity for CO-oxidation during SMSI/alloy formation as well as the reversibility by reoxidation will be investigated and compared to the changing structural and electronic characteristics.…”
Section: Introductionmentioning
confidence: 99%